2009
DOI: 10.1007/s00248-009-9621-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Functional Diversity Analysis of a Bauxite-Mined Restoration Chronosequence

Abstract: Soil microorganisms are sensitive to environmental perturbations such that changes in microbial community structure and function can provide early signs of anthropogenic disturbances and even predict restoration success. We evaluated the bacterial functional diversity of un-mined and three chronosequence sites at various stages of rehabilitation (0, 10, and 20 years old) located in the Mocho Mountains of Jamaica. Samples were collected during the dry and wet seasons and analyzed for metal concentrations, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 35 publications
5
33
2
Order By: Relevance
“…Organization: structural (preferably, bacteria and fungi, the two major soil microbial taxa) and functional (e.g., ammonium oxidizers) diversity measurements via genetic profiles (PCR-DGGE). After all, changes in soil microbial community structure and Downloaded by [Selcuk Universitesi] at 12:37 21 December 2014 function can provide early signs of anthropogenic disturbances and predict restoration success (Lewis et al 2010). 3.…”
Section: Higher-level Categoriesmentioning
confidence: 99%
“…Organization: structural (preferably, bacteria and fungi, the two major soil microbial taxa) and functional (e.g., ammonium oxidizers) diversity measurements via genetic profiles (PCR-DGGE). After all, changes in soil microbial community structure and Downloaded by [Selcuk Universitesi] at 12:37 21 December 2014 function can provide early signs of anthropogenic disturbances and predict restoration success (Lewis et al 2010). 3.…”
Section: Higher-level Categoriesmentioning
confidence: 99%
“…Claassens et al (), on the one hand, found no association between rehabilitation time and the structure and function of microbial communities. Other studies, however, report that the structure of bacterial communities in reclaimed soils more closely compares to that of nonmined sites, with increasing time after restoration (Harris & Birch ; Lewis et al ; Banning et al ; Li et al ). These findings are consistent with spontaneous primary succession observed on spoil heaps retrieved from depths of up to 200 m (Sourkova et al ; Pietrzykowski ; Urbanova et al ).…”
Section: Introductionmentioning
confidence: 95%
“…At present, the global best practice for reclamation of open‐cut mines dictates that topsoil is stockpiled for the shortest time possible and then used to overlay reconstructed landscapes during revegetation (Lewis et al ; Dangi et al ; Rai et al ; Commonwealth of Australia ; Harris ; Mushia et al ). This practice is thought to safeguard physicochemical and biological characteristics of topsoil and thereby reduce the additional costs, which are associated with rehabilitation of sites using degraded topsoils (Commonwealth of Australia ).…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: zhenghua@rcees.ac.cn to environmental perturbations (Harris, 2003;van Dijk et al, 2009;Lewis et al, 2010;Banning et al, 2011) because of its rapid response to anthropogenic disturbances relative to soil biogeochemical properties. These responses have been assessed using soil biological indicators such as the phospholipid fatty acid (PLFA) profiles to reflect the structure of the soil microbial community (Iovieno et al, 2010), and soil enzyme activities to reflect their functional capacity (Rivas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%